Policy Selectivity Forgone: Debt and Donor Behavior in Africa - Birdsall, Nancy; Claessens, Stijn; Diwan, Ishac (Washington, DC: World Bank, 2014)
Authors assess the dynamics behind the high net resource transfers by donors and creditors to Sub-Saharan African countries. Analyzing the determinants of overall net transfers for a panel of 37 recipient countries in 1978-98, Authors find that country policies mattered little. Donors especially bilateral donors actually made greater transfers to countries with high debt, largely owed to multilateral creditors, when policies were 'bad'. Authors conclude that comprehensive debt relief has the potential, though not the certainty, to restore selectivity in support of good policies. That would make development assistance more effective going forward and increase public support in donor countries.